Stability analysis and evaluation of staggered coupled analysis methods for electromagnetic and structural coupled finite element analysis. (1st January 2017) - Niho, Tomoya; Horie, Tomoyoshi; Uefuji, Junpei; Ishihara, Daisuke
Highlights: A stability evaluation method is proposed for magnetic damping vibration analysis. Numerical stability is examined by stable region for coupled analysis methods. Computing time required to obtain stable and converged solutions is compared. Abstract: The numerical stability of electromagnetic and structural coupled analysis methods is examined in terms of the spectral radius for various methods combined with a coupled algorithm, time integration methods for structural analysis and eddy current analysis, and coupled effect evaluation methods. The coupled analysis method with the conventional serial staggered algorithm, generalized– α method for structure, backward difference method for eddy current, and coupled effect evaluation using previous time step results is seen to be the most suitable from the viewpoints of stability and computing time. The stability of the conventional parallel staggered algorithm is found to be much improved if the generalized– α method is used for structural analysis.